1986
DOI: 10.2307/3899770
|View full text |Cite
|
Sign up to set email alerts
|

An 18-Year Comparison of Control Methods for Wyoming Big Sagebrush in Southwestern Montana

Abstract: Four Wyoming big sagebrush (Artem& tri&nW ssp. wyomingends Beetle and Young) control treatments: burning, spraag with 2,4-D, rotocutting, and plowing, along with no control (rest) were compared in southwestern Montana. Production date (excluding sagebrush) were collected 10 years and sagebrush canopy cover and understory basal cover were collected 8 years during the period 1963-1981. Sagebrush canopy was most effectively reduced by burning while plowing with seeding was least effective. Rest alone resulted in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
52
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 10 publications
(8 reference statements)
7
52
0
Order By: Relevance
“…This point is illustrated by Wambolt and Payne (1986) who compared four methods of Wyoming big sagebrush control. Wyoming big sagebrush recovered faster from plowing, rotocutting, and spraying with 2,4-D than when burned.…”
Section: Chemical Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…This point is illustrated by Wambolt and Payne (1986) who compared four methods of Wyoming big sagebrush control. Wyoming big sagebrush recovered faster from plowing, rotocutting, and spraying with 2,4-D than when burned.…”
Section: Chemical Controlmentioning
confidence: 99%
“…Eichhorn and Watts (1984, p. 32) reported: "burning removed big sagebrush (Artemisia tridentata wyomingensis) from the site and it has not reinvaded after 14 years." Wambolt and Payne (1986) reported that 18 years after a fire, Wyoming big sagebrush canopy cover was only 16 percent of control and significantly below other control methods. Fraas and others (1992) found little recovery of mountain big sagebrush on an 8-year-old burn.…”
Section: Recovery Of Big Sagebrush After Fire and Fire Interval _____mentioning
confidence: 99%
“…Most of these herbaceous plants located under shrub canopies must compete heavily with shrubs for resources (Reisner, 2010), and even though they are surviving, their ability to reproduce and spread is limited. Once this sagebrush and perennial grass relationship is achieved on a site, passive restoration may no longer be an option for restoring mixed stands of sagebrush and perennial grasslands (Rice and Westoby, 1978;West and others, 1984;Wambolt and Payne, 1986;Cagney and others, 2010). Targeted grazing may reduce sagebrush (Petersen and others, 2014), but perennial grass densities may be insufficient to produce new plants and fill the openings created by sagebrush (Wambolt and Watts, 1996).…”
Section: General Accounting Office 1977)mentioning
confidence: 99%
“…This implies that recovery of sagebrush will occur soon after burning. However, research on a variety of sagebrush control treatments in south-western Montana (McNeal, 1984;Wambolt and Payne, 1986;Watts and Wambolt, 1989;Fraas et al, 1992;Wambolt and Watts, 1996;Watts and Wambolt, 1996; and south-eastern Idaho (Harniss and Murray, 1973) found that big sagebrush recovery was prolonged, with completion sometimes taking as long as 30 years. This was true even in the absence of heavy browsing which further suppresses recovery (Wambolt, 1996;Wambolt and Sherwood, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…During the last 50 years the loss of millions of hectare of big sagebrush in the western United States from burning or other treatments to provide an anticipated advantage for herbaceous underEmail of corresponding author: cwambolt@montana.edu story species and thereby livestock forage has occurred. It is interesting that big sagebrush reduction by a variety of treatments has not always resulted in anticipated increases of herbaceous production (Blaisdell, 1953;Daubenmire, 1975;Peek et al, 1979;Anderson and Holte, 1981;Kuntz, 1982;McNeal, 1984;Mangan and Autenrieth, 1985;Sturges and Nelson, 1986;Wambolt and Payne, 1986;Fraas et al, 1992;Wambolt and Watts, 1996). Where herbaceous production has increased following sagebrush reduction, the cause of the increase is often difficult to determine.…”
Section: Introductionmentioning
confidence: 99%